Pengaruh Perspektif Generasi Z terhadap Keputusan Berinvestasi di Pasar Modal Syariah (Studi Kasus pada Mahasiswa FEBI UIN Fatmawati Sukarno Bengkulu) - Alen Tri Wahyuni; Asnaini Asnaini; Romi Adetio Setiawan (LABATILA: Jurnal Ilmu Ekonomi Islam, 2022)
The purpose of this study is to counter the results of KSEI's data in 2022 regarding the number of investors dominated by generation Z and the results of a survey conducted by KIC regarding the decisions of generation Z to invest in the Islamic Stock Exchange. The approach used is quantitative. The population in this study were students of” FEBI UIN Fatmawati Sukarno Bengkulu. The sampling technique used is quota sampling, which is the students of FEBI UIN Fatmawati Sukarno Bengkulu which amounts to 50 people who have or not a stock account. The results tested by SPSS 25, with a significance value of 0.109 > 0.05. However, the results of the research conducted, it concluded that the zero Hypothesis (H0) is accepted, which is perspective (X) variable has no significant effect on investment decisions (Y) variable in the Islamic Stock Exchange. The results also show that out of 50 respondents there are only 7 (14%) respondents who already have a stock account. They have a stock account admitted that did not understand the investment system and also the reason they opened a stock account only to fulfill their assignments. Meanwhile, 43 (86%) of them admitted did not interest in investing, apart from their perspective which was not very open to investing in the Islamic Stock Exchange, they also have no interest in knowing more about the investment system and they did not lesson of investing in Islamic Stock Exchange.